Search for a heavy neutral gauge boson in the dielectron channel with 5.4 fb(-1) of p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; et al. (Elsevier B.V., 2011)
We report the results of a search for a heavy neutral gauge boson Z' decaying into the dielectron final state using data corresponding to an integrated luminosity of 5.4 fb(-1) collected by the D0 experiment at the Fermilab Tevatron Collider. No significant excess above the standard model prediction is observed in the dielectron invariant-mass spectrum. We set 95 sigma(p (p) over bar -> Z') x BR(Z' -> ee) depending on the dielectron invariant mass. These cross section limits are used to determine lower mass limits for bosons in a variety of models. For the sequential standard model boson a lower mass limit of 1023 GeV is obtained. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Extensions of standard model; New gauge bosons